2022
DOI: 10.1016/j.euf.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific Membrane Antigen Biology in Lethal Prostate Cancer and its Therapeutic Implications

Abstract: Context: Prostate-specific membrane antigen (PSMA) is a promising, novel theranostic target in advanced prostate cancer (PCa). Multiple PSMA-targeted therapies are currently in clinical development, with some agents showing impressive antitumour activity, although optimal patient selection and therapeutic resistance remain ongoing challenges. Objective: To review the biology of PSMA and recent advances in PSMA-targeted therapies in PCa, and to discuss potential strategies for patient selection and further ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 92 publications
1
40
0
Order By: Relevance
“…PSMA is a protein overexpressed in PCa tumor cells, and this is the rationale for using PSMA-targeted agents in the diagnosis and therapy of PCa [ 6 , 7 ]. However, PSMA is even overexpressed in other tumors beyond PCa and in other organs and tissues [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSMA is a protein overexpressed in PCa tumor cells, and this is the rationale for using PSMA-targeted agents in the diagnosis and therapy of PCa [ 6 , 7 ]. However, PSMA is even overexpressed in other tumors beyond PCa and in other organs and tissues [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radioligand therapy with [177Lu]-PSMA-617 improves patients' overall survival by decreasing the risk of death in more than one-third of metastatic castration-resistant PCa patients [20][21][22] who have progressed after conventional treatments. Novel PSMA-targeting immunotherapies, small molecules, and antibody therapies are currently in clinical development, also in earlier stages of PCa, with emerging evidence of antitumor activity [23]. However, patient selection is crucial to avoid a false negative scan, thus optimizing health economic resources [24].…”
Section: Discussionmentioning
confidence: 99%
“…Akt serves as a major target to block prostate cancer growth, proliferation, adhesion, and invasion. A phase 2 clinical trial has shown that blocking Akt, compared to second-line chemotherapy [28], is associated with tumor shrinkage and delayed disease progression in the significant subset of patients with metastatic castration-resistant prostate cancer. Randomized trials combining an Akt inhibitor with androgen deprivation (abiraterone, enzalutamide) are currently underway [29].…”
Section: Discussionmentioning
confidence: 99%